Medical issues for female athletes returning to competition after childbirth - Nose-Ogura, S.; Yoshino, O.; Nakamura-Kamoto, H.; Kanatani, M.; Harada, M.; Hiraike, O.; Saito, S.; Fujii, T.; Osuga, Y. (The Physician and Sportsmedicine, 2024)
Background In recent years, the number of athletes who aim to return to competition after childbirth has increased. However, few international reports have investigated complications during pregnancy, and changes in physical function after childbirth in many athletes.